Unveiling three accessory spleens in one patient: a rare case report and literature review - Hamdah Hanifa; Hussein Alhussein; Lissa Mahmandar; Sara Kadi; Mahfoud Najjar; Ahmad Alhaj (International Journal of Emergency Medicine, 2024)
Abstract Background During embryogenesis, the spleen undergoes intricate developmental processes, originating from mesenchymal cells in the dorsal mesentery. An accessory spleen, a common anomaly found in autopsies and abdominal CT scans, can often be mistaken for different types of tumors. To the best of our knowledge, this is the first case in Syria documenting the occurrence of 3 accessory spleens in a patient who had previously undergone splenectomy. Case presentation A 33-year-old male presented with right hypochondrium pain, sharp and radiating to the right flank, exacerbated by movement and large meals. Past medical history included mild Irritable Bowel Syndrome (IBS) and splenectomy due to a traumatic accident in childhood. On admission, vital signs were stable, with abdominal tenderness in the right upper quadrant. Laboratory investigations showed normal values. Ultrasound revealed a lobulated mass at the right adrenal gland (4.5 × 5 cm) with an isoechoic to hypoechoic texture. Multi-slice computed tomography (MSCT) Scan showed multiple nodules in the right adrenal gland, regular in shape, exerting a compressive mass effect, and significant lymphadenopathy around the abdominal aorta. Elevated metanephrine levels raised suspicion of an extra-adrenal pheochromocytoma. Laparoscopic surgery was performed, revealing accessory spleens and normal adrenal tissue with no malignancy. Conclusion Healthcare providers should consider accessory spleens as a differential diagnosis for masses near the adrenal glands. Multiple accessory spleens in the adrenal region can complicate cases. Accessory spleens in uncommon locations like the adrenal glands can be challenging to diagnose and manage.